2015
DOI: 10.1007/s11695-015-1713-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Roux-en-Y Gastric Bypass and Sleeve Gastrectomy Surgery on Dietary Intake, Food Preferences, and Gastrointestinal Symptoms in Post-Surgical Morbidly Obese Lebanese Subjects: A Cross-Sectional Pilot Study

Abstract: There were no major differences in dietary intake and food preferences between RYGB and SG groups. There was a trend for sweet-eating in SG subjects with less dumping symptoms to suggest different mechanisms of action for each procedure, which might impact eating behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 59 publications
8
23
2
5
Order By: Relevance
“…In contrast, a number of other studies have reported no changes in food preference after RYGB and VSG. A retrospective cross-sectional study compared food intake and food preferences over 1 yr, and patients reported no difference in dietary intake and food preferences between RYGB and VSG groups (90). This agrees with the longest follow-up study of 5 yr also comparing VSG and RYGB (199) where patients reported the percentages of macronutrients were not significantly different between the two surgical groups (199).…”
Section: E Food Preferencessupporting
confidence: 75%
“…In contrast, a number of other studies have reported no changes in food preference after RYGB and VSG. A retrospective cross-sectional study compared food intake and food preferences over 1 yr, and patients reported no difference in dietary intake and food preferences between RYGB and VSG groups (90). This agrees with the longest follow-up study of 5 yr also comparing VSG and RYGB (199) where patients reported the percentages of macronutrients were not significantly different between the two surgical groups (199).…”
Section: E Food Preferencessupporting
confidence: 75%
“…Studies comparing the effect of RYGB and SG surgery on food preferences are scarce. In a pilot study, El Labban et al did not detect any major differences in food intake and preferences between RYGB and SG operated patients . Nance et al compared pre‐ to postoperative changes in eating behavior and detected similar changes after RYGB and SG surgery .…”
Section: Discussionmentioning
confidence: 99%
“…LSG-Patienten und LRYMB-Patienten unterscheiden sich selten signifikant. Auch El Labban et al haben keine Präferenzunterschiede für Lebensmittel festgestellt [36]. Da zwischen beiden OP-Arten keine Unterschiede in der Präferenz für Lebensmittel vorliegen, gibt es aus Sicht der Lebensmittelwahl keine "gesündere" Operationsart.…”
Section: Lebensmittelauswahlunclassified
“…Da die LRYMP-Patienten ihre Getränkezufuhr postoperativ nicht verändern, kommt es zu Mo 3 und Mo 6 zu einem signifikanten Unterschied zwischen den beiden Gruppen. Diese entspricht auch dem Ergebnis von El Labban et al [36]. Aus diesem Ergebnis lässt sich schließen, dass vor allem bei LSG-Patienten postoperativ in der Beratung auf eine ausreichend hohe Getränkezufuhr geachtet werden muss.…”
Section: Lebensmittelgruppenunclassified
See 1 more Smart Citation